2022
DOI: 10.1021/acsanm.2c04531
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Multimode Detection of pH and Fe3+ by Dual-Emissive Heteroatom-Doped Carbon Dots for Living Cell Applications

Abstract: Dual-emissive carbon dots (D-CDs) are in high demand for multipurpose applications. Herein, nitrogen-doped carbon dots possessing inherent dual emissions at green (490 nm) and yellow (570 nm) are synthesized hydrothermally from 3,4-diaminobenzoic acid and hydrazine hydrate. The relative intensity of the two emission bands is dependent markedly on the pH of medium, making the D-CDs a robust pH sensor within the pH range of 2.0−7.6. The ratiometric emission of D-CDs is sensitive to trace amounts of Fe 3+ ; the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…There are several phenomena [e.g., Förster resonance energy transfer (FRET), inner-filter effect (IFE), and ground-state complexation] reported in the literature that can cause quenching of the fluorescence intensity of a fluorophore . The above-mentioned events can be categorized into two parts: static and dynamic quenching. , Excited-state collisions between the quencher and the fluorophore can cause dynamic quenching, and if they are tightly bound, then static quenching occurs . These two quenching processes can be differentiated by measuring the fluorescence lifetimes of the fresh and analyte-treated fluorophores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several phenomena [e.g., Förster resonance energy transfer (FRET), inner-filter effect (IFE), and ground-state complexation] reported in the literature that can cause quenching of the fluorescence intensity of a fluorophore . The above-mentioned events can be categorized into two parts: static and dynamic quenching. , Excited-state collisions between the quencher and the fluorophore can cause dynamic quenching, and if they are tightly bound, then static quenching occurs . These two quenching processes can be differentiated by measuring the fluorescence lifetimes of the fresh and analyte-treated fluorophores.…”
Section: Resultsmentioning
confidence: 99%
“…The huge difference between the observed and the corrected quenching efficiencies strongly suggested that the IFE contribution is required to explain the observed quenching efficiency in the presence of 6-MP. Although the IFE was once thought to be a flaw in fluorescence measurement, it has now been discovered to be a non-irradiative energy transformation model in the spectroscopic technique and has been utilized in the creation of numerous photoluminescent-based detection systems. , Moreover, this sensing mechanism has been reported in many of the previously reported literature studies for 6-MP and other analytes’ sensing. , …”
Section: Resultsmentioning
confidence: 99%
“…We have cited additional references within the Supporting Information [51–88] . The Supporting Information includes: 1.…”
Section: Supporting Information Summarymentioning
confidence: 99%
“…[1][2][3] Since their discoveries, CDs have widened their application in LEDs, fingerprinting, room-temperature phosphorescence, solar cells, sensing, etc. [4][5][6][7] On the one hand, to date, most of the reported CDs showed fluorescence only in dispersed states, which restricts their applicability. 8,9 The dispersed CDs generate aggregationcaused quenching when it turns into solid powder due to p-p stacking interactions, Fo ¨rster resonance energy transfer, and intermolecular hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%